Praxis, Doxa and research methods: Reconsidering critical accounting. (November 2015) - Everett, Jeff; Neu, Dean; Rahaman, Abu Shiraz; Maharaj, Gajindra
Abstract: This essay examines the critical accounting field's current reliance on qualitative methods, asking whether these methods are necessarily better than quantitative methods. The notion of praxis and the purpose of critical research are discussed and the pros and cons of quantitative methods in relation to this notion and purpose are considered. The taxonomy of critical accounting and its ontological and epistemological assumptions are reviewed in order to problematize the field's doxa, or taken-for-granted understanding of how critical research ought to be conducted. Examples are provided of two theoretical perspectives that rely on quantitative and mixed methods (critical realism and Bourdieu's praxeology), and a number of research questions that are conducive to the use of quantitative and mixed methods are identified.